Wildlife Conservation and Management in Kenya: Towards a Co-management Approach - John Mburu (Fondazione Eni Enrico Mattei (FEEM), 2004)
The co-management approach of managing natural resources has increasingly become popular among conservationists and development practitioners since it overcomes the shortcomings of both the centralised management and community-based approaches that hinder harmonization of conflicting interests among diverse stakeholder groups. Considering criteria developed from theoretical advancements on co-management and drawing on empirical studies conducted in Kenya, the paper examines how successful the co-management approach has been in terms of meeting the needs and interests of local communities and conservationists. Further, it analyses some of the factors or conditions that contribute towards the emergence and subsequent adoption of the co-management approach in the conservation and management of wildlife. These factors, which may also be important in other developing countries, include the provision of a favourable policy framework, institutional capacity of organized user groups to co-manage wildlife resources, land tenure conditions and accessibility to wildlife resources. It is emphasised that the co-management approach has had, so far, mixed results and there are certain important factors challenging its successful implementation in Kenya.
Keywords: R00; Q20; 330; Kenya; Co-management; Wildlife management; Conditions for co-management; Sustainable management; Wildtierschutz; Kenia